Characterization of two coleopteran alpha-amylases and molecular insights into their differential inhibition by synthetic alpha-amylase inhibitor, acarbose - Channale, Sonal M.; Bhide, Amey J.; Yadav, Yashpal; Kashyap, Garima; Pawar, Pankaj K.; Maheshwari, V. L.; Ramasamy, Sureshkumar; Giri, Ashok P. (Insect Biochemistry and Molecular Biology, 2016)
Post-harvest insect infestation of stored grains makes them unfit for human consumption and leads to severe economic loss. Here, we report functional and structural characterization of two coleopteran alpha-amylases viz. Callosobruchus chinensis alpha-amylase (CcAmy) and Tribolium castaneum alpha-amylase (TcAmy) along with their interactions with proteinaceous and non-proteinaceous alpha-amylase inhibitors. Secondary structural alignment of CcAmy and TcAmy with other coleopteran alpha-amylases revealed conserved motifs, active sites, di-sulfide bonds and two point mutations at spatially conserved substrate or inhibitor binding sites. Homology modeling and molecular docking showed structural differences between these two enzymes. Both the enzymes had similar optimum pH values but differed in their optimum temperature. Overall, pattern of enzyme stabilities were similar under various temperature and pH conditions. Further, CcAmy and TcAmy differed in their substrate affinity and catalytic efficiency towards starch and amylopectin. HPLC analysis detected common amylolytic products like maltose and maltotriose while glucose and malto-tetrose were unique in CcAmy and TcAmy catalyzed reactions respectively. At very low concentrations, wheat alpha-amylase inhibitor was found to be superior over the acarbose as far as complete inhibition of amylolytic activities of CcAmy and TcAmy was concerned. Mechanism underlying differential amylolytic reaction inhibition by acarbose was discussed. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Acarbose; alpha-amylase; alpha-amylase inhibitor; Callosobruchus chinensis; Coleoptera; Tribolium castaneum